A systematic scoping review on utility of cytomorphometry in the detection of dysplasia in oral potentially malignant disorders - Monal Yuwanati; Amol Gadbail; Shailesh Gondivkar; Sachin C. Sarode; Ravi Dande; Shubhangi Mhaske; Satayjit Tekade; Sandeep Kumar Pathak (Journal of Oral Biology and Craniofacial Research)
Background: Oral exfoliative cytology is simple, non-invasive, inexpensive tools prone to subjective bias. Objective computer-based quantitative cytomorphometry technique was developed in last few decades to overcome its limitation. However, there is no consensus about the utility of cytomorphometry as a routine screening tool for early detection of dysplastic changes. Objectives: To review the utility of cytomorphometry in OPMDs in the detection of dysplasia changes. Method: A scoping review was undertaken focusing on cytomorphometric analysis in exfoliative cells for detection of oral epithelial dysplasia and cytomorphometric parameter denoting dysplasia. The systematic search was carried out in the online journal databases (Scopus, Google Scholar, PubMed, Web of Science) using keywords until December 2019 for the studies evaluated the cytomorphometry in the detection of dysplastic changes in OPMDs. Three authors independently extracted data using collection forms. Result: The search strategy found seven analytical cross-sectional studies for scoping review after eliminating 8940 out of 8947 initial results. The scoping review showed that cytomorphometry is useful tool in detecting the dysplastic changes in OPMDs. In addition, decrease in mean cellular area, increase in mean nuclear area, and decrease in mean cell diameter, increase mean nuclear diameter, increase in mean nuclear and cytoplasmic area ratio, associated with development of dysplastic changes in OPMDs. Conclusion: Cytomorphometry is promising tool, yet there is currently no-good evidence to support role of cytomorphometry in detecting the dysplastic changes in OPMDs in this setting. More research is required for refinement of cytomorphometry as a screening tool.